2020
DOI: 10.3390/nu12113350
|View full text |Cite
|
Sign up to set email alerts
|

Food Sources and Dietary Quality in Small Island Developing States: Development of Methods and Policy Relevant Novel Survey Data from the Pacific and Caribbean

Abstract: Small Island Developing States (SIDS) have high and increasing rates of diet-related diseases. This situation is associated with a loss of food sovereignty and an increasing reliance on nutritionally poor food imports. A policy goal, therefore, is to improve local diets through improved local production of nutritious foods. Our aim in this study was to develop methods and collect preliminary data on the relationships between where people source their food, their socio-demographic characteristics and dietary qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 24 publications
1
47
0
Order By: Relevance
“…Because this previous study investigated individual food security rather than household food insecurity and did not adjust for potential confounders of the association, it may not be directly comparable to our current study; nonetheless, the previous study identified an association between food source and food security [ 32 ]. Our observation of an association of food source with dietary diversity is consistent with other existing studies [ 29 , 33 , 34 , 35 , 36 ]. However, the specific food sources investigated were not always commensurate with those in this study, likely due to country differences, food outlet classification and the prevalence of use of different food sources in different study samples.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Because this previous study investigated individual food security rather than household food insecurity and did not adjust for potential confounders of the association, it may not be directly comparable to our current study; nonetheless, the previous study identified an association between food source and food security [ 32 ]. Our observation of an association of food source with dietary diversity is consistent with other existing studies [ 29 , 33 , 34 , 35 , 36 ]. However, the specific food sources investigated were not always commensurate with those in this study, likely due to country differences, food outlet classification and the prevalence of use of different food sources in different study samples.…”
Section: Discussionsupporting
confidence: 93%
“…This dietary diversity indicator presents minimum dietary diversity ‘as a proxy to micronutrient adequacy’ for women of reproductive age [ 28 ]. Precedent for the use of MDD-W as a pragmatic approach to assess dietary diversity in adults in low resource settings can be found in a recent study [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…We then applied this typology to analysis of a large nationally representative survey of food acquisition in Solomon Islands to quantify, for the first time, the reliance of different population groups on different FEs and the role they play in contributing to diet quality. This is a significant contribution to the literature as there are few studies that examine the relationship between FE types and diet quality in the Pacific region (e.g., [26,42]) and no studies to our knowledge that examine this relationship across all the relevant FEs presented here. The cultivated FE is by far the most important source of food in Solomon Islands providing 60% of the quantity and 33% of the value of food acquired nationally.…”
Section: Discussionmentioning
confidence: 95%
“…In order to describe the sources of food acquisition in the Pacific region, we adapt existing conceptual frameworks of FEs [12,14,26] to the Pacific context. The framework by Turner et al [12] distinguishes between the 'external' and 'personal' FE whereby the external domain includes characteristics such as food availability, prices and vendor properties, whilst the personal FE is determined by individual level factors that interact with the external FE such as accessibility, affordability and desirability.…”
Section: Conceptual Typology Of Food Environmentsmentioning
confidence: 99%
See 1 more Smart Citation